2020
DOI: 10.37358/mp.20.1.5309
|View full text |Cite
|
Sign up to set email alerts
|

Self-adhesion X-ray Shielding Composite Material of EPDM Rubber with Barite: Mechanical Properties

Abstract: It is actual now to work out new radiation protecting sheeting on the basis of non-curing polymeric composition which possess self-adhesion properties, are easily mounted and dismantled and provide high tightness and low permeability. Mechanical properties of non-curing composites consisting of ethylene propylene diene monomer (EPDM), industrial oil (IO), alkyl phenol-formaldehyde resin (PF) with addition of barite (52 %) to the total material volume were investigated in this article. The aim of investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, shielding equipment, such as personal protective equipment (PPE) and covers for transporting casks, requiring exceptional flexibility, high strength, and a large amount of elongation from the materials, relies on natural and synthetic rubber composites. For example, Bi 2 O 3 /NR, Bi 2 O 3 /EPDM, BaSO 4 /EPDM, and W/SR composites were among recently developed X-ray shielding rubber materials that offered not only effective X-ray attenuation abilities but also sufficient mechanical strength and flexibility to the users [13][14][15][16]. Notably, these mentioned examples of X-ray shielding materials are lead-free, which is presently sought-after in materials, as they could substantially reduce the risks to users from exposure to highly toxic lead (Pb) elements and compounds that are common protective fillers used for the manufacturing of X-ray and gamma shielding materials due to their economical accessibility and excellent attenuation capability [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, shielding equipment, such as personal protective equipment (PPE) and covers for transporting casks, requiring exceptional flexibility, high strength, and a large amount of elongation from the materials, relies on natural and synthetic rubber composites. For example, Bi 2 O 3 /NR, Bi 2 O 3 /EPDM, BaSO 4 /EPDM, and W/SR composites were among recently developed X-ray shielding rubber materials that offered not only effective X-ray attenuation abilities but also sufficient mechanical strength and flexibility to the users [13][14][15][16]. Notably, these mentioned examples of X-ray shielding materials are lead-free, which is presently sought-after in materials, as they could substantially reduce the risks to users from exposure to highly toxic lead (Pb) elements and compounds that are common protective fillers used for the manufacturing of X-ray and gamma shielding materials due to their economical accessibility and excellent attenuation capability [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, lead is considered a hazardous chemical [6]. Recently, the radiation shielding materials with the addition of fillers such as tungsten oxide (W 2 O 3 ) [7][8], bismuth oxide (Bi 2 O 3 ) [8][9][10], and barium sulfate (BaSO 4 ) [7,[11][12] were studied for replacement of lead (Pb). Among these materials, BaSO 4 is an exciting filler since it is environmentally friendly, safe, and highly effective in X-ray attenuation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the radiation shielding materials with the addition of fillers such as tungsten oxide (W 2 O 3 ) [7][8], bismuth oxide (Bi 2 O 3 ) [8][9][10], and barium sulfate (BaSO 4 ) [7,[11][12] were studied for replacement of lead (Pb). Among these materials, BaSO 4 is an exciting filler since it is environmentally friendly, safe, and highly effective in X-ray attenuation [12]. Previous investigations reported that it could be improved the radiation shielding properties of concrete [13] and it is also found that a shielding film prepared from BaSO4 and polymeric silicon has higher tensile strength and X-ray shielding performance [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the rail pads are made of rubber, ethylene propylene diene monomer (EPDM), thermoplastic polyester elastomer (TPE), high-density polyethylene (HDPE), and ethylene-vinyl acetate (EVA), as presented in Figure 2 [7,8]. Such materials are well known in industry and these are extensively studied from many view points to solve various practical issues [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%